A study of racial/ethnic differences in treatment preferences among lupus patients - Vina, Ernest R. (Oxford University Press, 2012)
Objectives. To determine whether there are racial/ethnic differences in the willingness of SLE patients to receive CYC or participate in clinical trials, and whether demographic, psychosocial and clinical characteristics contribute to these differences. Methods. Data from 120 African-American and 62 white lupus patients were evaluated. Structured telephone interviews were conducted to determine treatment preferences, as well as to study characteristics and beliefs that may affect these preferences. Data were analysed using serial hierarchical multivariate logistic regression and deviances were calculated from a saturated model. Results. Compared with their white counterparts, African-American SLE patients expressed less willingness to receive CYC (67.0% vs 84.9%, P = 0.02) if their lupus worsened. This racial/ethnic difference remained significant after adjusting for socioeconomic and psychosocial variables. Logistic regression analysis showed that African-American race [odds ratio (OR) 0.29, 95% CI 0.10, 0.80], physician trust (OR 1.05, 95% CI 1.00, 1.12) and perception of treatment effectiveness (OR 1.40, 95% CI 1.22, 1.61) were the most significant determinants of willingness to receive CYC. A trend in difference by race/ethnicity was also observed in willingness to participate in a clinical trial, but this difference was not significant. Conclusion. This study demonstrated reduced likelihood of accepting CYC in African-American lupus patients compared with white lupus patients. This racial/ethnic variation was associated with belief in medication effectiveness and trust in the medical provider, suggesting that education about therapy and improved trust can influence decision-making among SLE patients.